Meningkatkan Motivasi Belajar Anak Usia Dini di Era digital melalui Program Macromedia Flash 8 - Kasmiati; Rahman (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2022)
In the digital era and post-Covid-19 pandemic, educators have become friendly and sensitive in using technology in learning. The design of learning media using macromedia flash 8 can create an interesting and fun learning process and increase early childhood learning motivation. This research was conducted using classroom action (CAR) with four main steps of action research, namely: Planning (Planning), Implementation (Observation), Implementation (observation) and Reflecting (Reflecting). The number of research subjects was 17 children in class B in PAUD Pinang Masak. Collecting data using observation guidelines to measure the achievement of the cycle and analysis using the percentage formula. The results showed that the students of Kindergarten B Pinang Masak Jambi University using the macromedia flash 8 program in teaching showed an increase in learning motivation.